Butyrate and trichostatin A effects on the proliferation/differentiation of human intestinal epithelial cells: induction of cyclin D3 and p21 expression. Issue 4 (1st April 2000) - Siavoshian, S; Segain, J-P; Kornprobst, M; Bonnet, C; Cherbut, C; Galmiche, J-P; Blottière, H M
Abstract : BACKGROUND: Sodium butyrate, a product of colonic bacterial fermentation, is able to inhibit cell proliferation and to stimulate cell differentiation of colonic epithelial cell lines. It has been proposed that these cellular effects could be linked to its ability to cause hyperacetylation of histone through the inhibition of histone deacetylase. AIM: To analyse the molecular mechanisms of butyrate action on cell proliferation/differentiation and to compare them with those of trichostatin A, a well known inhibitor of histone deacetylase. METHODS: HT-29 cells were grown in the absence or presence of butyrate or trichostatin A. Cell proliferation and cell cycle distribution were studied after DNA staining by crystal violet and propidium iodide respectively. Cell cycle regulatory proteins were studied by western blot and reverse transcription-polymerase chain reaction. Cell differentiation was followed by measuring brush border enzyme activities. Histone acetylation was studied by acid/urea/Triton acrylamide gel electrophoresis. RESULTS: Butyrate blocked cells mainly in the G1 phase of the cell cycle, whereas trichostatin A was inhibitory in both G1 and G2 phases. Butyrate inhibited the mRNA expression of cyclin D1 without affecting its protein expression and stimulated the protein expression of cyclin D3 without affecting its mRNA expression. Trichostatin A showed similar effects on cyclin D1 and D3. Butyrate and trichostatin A stimulated p21 expression both at the mRNA and protein levels, whereas their effects on the expression of cyclin dependent kinases were slightly different. Moreover, butyrate strongly stimulated the activity of alkaline phosphatase and dipeptidyl peptidase IV, whereas trichostatin A had no effect. Finally, a six hour exposure to butyrate or trichostatin A induced histone H4 hyperacetylation. At 15 and 24 hours, histone H4 remained hyperacetylated in the presence of butyrate, whereas it returned to control levels in the presence of trichostatin A. CONCLUSIONS: The data may explain how butyrate acts on cell proliferation/differentiation, and they show that trichostatin A does not reproduce every effect of butyrate, mainly because of its shorter half life.